THE URGENCY OF USING AUDIOBOOK IN GENERAL COURSE LEARNING - Jaka Warsihna; Wang Dandan; E Oos M Anwas; Maman Suryaman; Fauzy Rahman Kosasih; Andi Amri; Zulmi Ramdani (Universitas Negeri Yogyakarta, 2021)
This study was aimed to explore the urgency of using audiobook in general course learning as a form of distance learning manifestation. This research was conducted descriptively. The research subjects involved in this study were students at the Open University. A total of 294 respondents were selected through the purposive sampling technique. This study used a closed questionnaire created and modified by the researcher based on an exploratory structure and also used a theoretical basis on the use of audiobooks in learning. The results show that most respondents agreed that the use of audiobooks in learning is a positive breakthrough that can arouse their interest and interest in being active in learning. In addition, respondents also agreed that the use of this audiobook must be strengthened by various important elements such as the material to be delivered, the selected voice actors, and the duration of time to be used. The audiobook is feasible learning media for those who cannot directly read the module and can be used in any situation so that the urgency is even greater if it is done in distance learning.